ANALYSES OF CHARATER AND CHARACTERIZATION OF THE NOVEL “LOVE BENEATH THE WINGS” BY KEZIA NADIRA PUBLISHED ON 2013 - Agustinus Lia Masan; Lisa A.G. Loupatty; Vantri Pieter Kelelufna (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2020)
The research with the title of analysis character and characterization in the novel "Love Beneath The Wings" by Kezia Nadira Published On 2013 aims to describe and explain: (1) characters in the novel Love Beneath The Wings by Kezia Nadira; (2) characterizations in the novel Love Beneath The Wings by Kezia Nadira. This Research Uses an Objective Study of Literature. The approach used in this research is descriptive qualitative research which is. The data in this study are in the form of words, sentences in the form of expressions, which are the focus of the research. Sources of data in this study are source documents, such as literary theory books, and the novel Love Beneath The Wings by Kezia Nadira. Data collection techniques in qualitative research use several steps. Data Analysis Techniques In This Research Using Interactive Analysis Techniques In The Form Of Data Reduction, Data Presentation, And Drawing Conclusions.